Why do Chinese women experience gamophobia? Psychoanalytic theory assisted discourses analysis - Chang, Joanna Nian (Frontiers in Psychology, 2024)
Social media is currently abuzz with discussions about the topic of women's gamophobia in China. Nevertheless, there is few research investigating gamophobia from a psychological perspective. This study utilizes content analysis and sentiment analysis to examine and analyze 857 individuals' texts about gamophobia on Little Red Book and uses psychoanalytic theory, which is centered on comprehending and interpreting the psychological processes of the human mind, to investigate the elements that contribute to women's gamophobia, aiming to address this knowledge gap. This investigation revealed that gamophobia might exert physical, psychological, and several other effects on individuals. This study employs a psychoanalytic framework and concludes that the rise of independent consciousness, many unhappy marriages in their environment, anxiety about dealing with unfamiliar family relationships, pursuit of personal and professional development, original family issues, changing perceptions of aging care, the media effect, the concept of parenthood, and criteria for choosing a life partner are the nine primary factors contributing to women’s gamophobia. To address the societal issues and outcomes resulting from a fear of marriage, it is advisable for those who experience this phobia to examine their negative defensive mechanisms and prioritize rational thinking in their mindset. Moreover, the Government should establish a social atmosphere that ensures women are neither influenced nor constrained by the media. Furthermore, promote holistic family education to bolster the self-awareness and prospective family comprehension of young individuals. Finally, government departments should also offer promotion and supporting measures to help assuage women's concerns about marriages.